2010
DOI: 10.1007/s11270-010-0505-y
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pb(II), Cr(III) and Cr(VI) from Aqueous Solutions Using Alum-Derived Water Treatment Sludge

Abstract: The sorption of Pb(II), Cr(III) and Cr(VI) from aqueous solution using alum-derived water treatment sludge was investigated using the batch adsorption technique. Samples of sludge from two separate water treatment plants were used (one where alum was used alone and one where it was used in combination with activated C). The sorption characteristics of the two samples were generally very similar. Sorption isotherm data for all three ions fitted equally well to both Freundlich and Langmuir equations. Maximum sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 34 publications
4
54
2
Order By: Relevance
“…It was evident that the fractional uptake of arsenic significantly increased with the increasing DWTS dosage (Figure 1a,c), and reached a complete removal at high sorbent dosage with an abundant surface area and number of available sorption sites [31].…”
Section: Effect Of Dwts Dosagementioning
confidence: 97%
See 3 more Smart Citations
“…It was evident that the fractional uptake of arsenic significantly increased with the increasing DWTS dosage (Figure 1a,c), and reached a complete removal at high sorbent dosage with an abundant surface area and number of available sorption sites [31].…”
Section: Effect Of Dwts Dosagementioning
confidence: 97%
“…The chemisorption of arsenic onto DWTS could encompass the specific sorption and surface precipitation at high arsenic concentrations, significantly enhancing the level of arsenic sorption [31].…”
Section: Effect Of Initial Arsenic Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also potential for WTRs use as a sorbent for metals and metalloids. Studies have shown that WTRs can adsorb As (Makris et al 2006;Gibbons and Gagnon 2011;Castaldi et al 2014), Cr (Zhou and Haynes 2011), Hg (Hovsepyan and Bonzongo 2009), Pb (Zhou and Haynes 2011;Putra and Tanaka 2011), and Se (Ippolito et al 2009) from solution. Moreover, results of several investigations of WTRs use to mitigate metal pollution in soils indicate that amendment with WTRs can increase the stability of Cd, Ni, Zn, Pb, Cu, Cr, and As in soils (Brown et al 2005;Sarkar et al 2007;Fan et al 2011;Nielsen et al 2011;Wang et al 2012b;Chiang et al 2012;Elkhatib et al 2013).…”
Section: Introductionmentioning
confidence: 99%